OCCUPATIONAL THERAPY OF DRINK-MAKING SKILLS EFFECTIVE TO INCREASE LEVEL OF INDEPENDENCE AMONG MENTAL DISORDERS PEOPLE - Cristin Wiyani; Endang Nurul Syafitri; Ririn Wahyu Widayati; Siti Fadlilah; Wayan Ni Luh Dian (Jurnal Keperawatan Respati Yogyakarta, 2022)
This study aims to determine the effects of the occupational therapy of drink-making skills on the level of independence among people with mental disorders at Kota Gede 1 Public Health Center Yogyakarta. This study used a quantitative quasi-experimental research with a pretest-posttest design without the control group design. The research population was all people with mental disorders in Purbayan and Prenggan Villages. A consecutive sampling technique was used to obtain samples of 15 people. Data were analyzed using the Wilcoxon test. The research instruments were questionnaires on independence and the occupational therapy SOPs for making thai tea drinks. The level of independence among people with mental disorders showed an increase with the mean score of pre-test of 2.53 and posttest of 2.93. the effects of occupational therapy on the level of independence indicated a p-value of 0.034. There was an effect of the occupational therapy of drink-making skills on the level of independence among people with mental disorders in Kota Gede 1 Public Health Center Yogyakarta. Keywords: Level of Independence; Occupational Therapy; Mental Disorders.